Experimental analysis on drilling process of CFRP composite laminates - Latifah, Md Yusoff (2008)
The principal aim of this work is to optimize the drilling process of composite materials namely carbon fiber reinforced plastics (CFRP). Aspects of tool materials and machining parameters on their influence against the thrust force and delamination were investigated. The chosen machining parameters are feed rate and spindle speed. The optimization process was achieved by a method called General factorial. Through analysis function (ANOVA) the factorial model was found to be significant since the P value is 0.0116 which is less than 0.05. Type of tools is the most significant factor followed by spindle speed. The less significant factor is feed rate. The optimal parameters were SPF tool, 2000 rpm of spindle speed and 400 mm/min of feed rate. The optimization result shows that this method was reliable with desirability 0.815. It was found that the optimization process is achieved by Factorial Design.